Aviation and Its Management Global Challenges and Opportunities - Sikander, Arif (IntechOpen, 2019)
Aviation has grown leaps and bounds within the last decade. Aviation courses and training at all levels have shown an exponential increase around the globe. There has been a restricted focus on writing books in this sector of the economy, mainly due to the shortage of expertise in this specialist and complex area. This book was written with the purpose of meeting this need of the aviation sector. Due to the diversified nature of aviation knowledge, which includes flying, engineering, airports, allied trades for aircraft and airports, airline and airport management and operations, education, etc., one text alone will not suffice and do justice to address all these areas. It is envisaged to develop subsequent parts of this book to cover all these knowledge areas. This book is the first installment of any subsequent books and explores issues including airline management and operations, airline business models, airport systems, flight operational procedures, aircraft maintenance, runway safety management systems, and air traffic management. In particular, attention will be given to aspects such as analysis of air traffic in a domestic market, runway safety management systems, critical success factors for multiple MRO service providers, key pain points of the industry to be addressed to move into the future, new research on hub airports for international flights, new business models for airlines, and runway safety management systems. This book is useful to aviation managers, educators, students, and professionals interested in any of the above issues.